Ultra‐Rapid Removal of Pb(II) Ions by a Nano‐MoS2 Decorated Graphene Aided by the Unique Combination of Affinity and Electrochemistry. (9th May 2022) - Arya Nair, J. S.; Saisree, S.; Sandhya, K. Y.
Abstract: Cost‐effective adsorbent materials with high Pb(II) removal efficiency and selectivity are considered necessary for successfully removing Pb(II) contamination from drinking water because of their high‐level toxicity and the ultra‐low safe level of ≤10 ppb in water. This study demonstrates the synthesis and the ultrafast Pb(II) removal capability of a partially reduced graphene oxide‐nano‐molybdenum disulfide composite (prGO‐MoS2 ). The prGO‐MoS2 exhibits thin sheets of prGO covered more or less uniformly with nano‐MoS2, and the open architecture gives enhanced accessibility to the S 2– and oxygen moieties present in prGO‐MoS2 . A single treatment of contaminated water samples with prGO‐MoS2 rapidly decreases the concentration of Pb(II) from 10 000 ppb to 0.8642 ppb within ≤3 min with an efficiency of ≥99.99% (4 log reduction value) at a V/m ratio of 2000 mL mg −1 . Among the reported materials for Pb(II) removal, prGO‐MoS2 exhibits the fastest removal speed (≤3 min) and the second‐highest adsorption capacity (762 mg g −1 ), and the highest distribution coefficient ( K d = 6.0 × 10 8 mL g −1 ). Here, the high removal performance of Pb(II) by prGO‐MoS2 is delineated based on affinity between Pb(II) and S 2− and oxygen moieties, electrochemistry, and the unique structural characteristics. Abstract : An adsorbent material, partially reduced graphene oxide‐nano‐molybdenum disulfide composite, is developed and demonstrated for the selective and ultra‐rapid removal of Pb (II) ions from contaminated environmental water samples, which decreases the concentration of Pb (II) from 10 000 to 0.8642 ppb within ≤3 min.